Expression levels of heat shock protein 60 and glucose-regulated protein 78 in response to trimethylamine-N-oxide treatment in murine macrophage J774A.1 cell line - Mohammadi, A; Gholamhoseyniannajar, A; Yaghoobi, M M; Jahani, Y; Vahabzadeh, Z (Cellular and Molecular Biology, 2015)
Trimethylamine N-oxide (TMAO), a common metabolite in animals and humans, can induce changes in the expression or conformation of heat shock proteins. It has also been introduced as a risk factor for atherosclerosis and a biomarker for kidney problems. On the other hand, increased levels of heat shock proteins 60 and 70 KDa are associated with increased atherosclerosis risk. This study was therefore designed to evaluate the possible effect(s) of TMAO on the expression of HSP60 and GRP78 at the mRNA and protein levels. Murine macrophage J774A.1 cells were treated with micromolar concentrations of TMAO and 4-phenylbutyric acid (4-PBA), a chemical chaperon, for different time intervals. Tunicamycin was also used as a control for induction of endoplasmic reticulum stress. Tunicamycin greatly increased both mRNA and protein levels of GRP78. Similarly but to a lesser extent compared to tunicamycin, TMAO also increased mRNA and protein levels of GRP78 in a dose and time-dependent manner. In contrast, 4-PBA failed to induce any changes. Similar to GRP78, HSP60 was also increased only at mRNA level in TMAO treated cells. 4-PBA also increased HSP60 mRNA levels, whereas, tunicamycin did not show any effect on either protein or mRNA levels of HSP60. Since both heat shock proteins are stress inducible and the elevation of GRP78 is a hallmark for endoplasmic reticulum stress induction, it can be concluded that TMAO may induce endoplasmic reticulum stress or may act through elevation of these heat shock proteins.